Complement and kidney disease, new insights. Issue 3 (May 2021) - Medjeral-Thomas, Nicholas R.; Pickering, Matthew C.; Cook, H. Terence
Abstract : Purpose of review: In this review, we discuss recent studies showing the importance of the complement pathway in kidney disease. Recent findings: Recent findings in C3 glomerulopathy (C3G) include: acute postinfectious glomerulonephritis is characterised by the presence of antifactor B antibodies; human leukocyte antigen type, but not rare complement gene variation, is associated with primary immunoglobulin-associated membranoproliferative GN and C3G. Immunohistochemistry in C3G shows that factor H related protein 5 (FHR5) is the most prevalent complement protein and correlates with kidney function. A multicentre study supported the use of mycophenolate mofetil (MMF) in C3G even after a propensity matching analysis. In immunoglobulin A nephropathy (IgAN) several studies have emphasised the importance of complement. Imbalances of circulating FH and FHR1 and FHR5, which interfere with the regulatory functions of FH, associate with IgAN. Immunohistochemistry has shown associations between glomerular FHR5 deposition and C3 activation; glomerular FHR5 associated with clinical markers of IgAN severity. Data also suggest the lectin complement pathway contributes to IgAN severity. We also discuss complement activation in thrombotic microangiopathy and other kidney diseases. Summary: Complement activity can be detected in a wide range of kidney diseases and this provides pathogenic insight and potential for therapy with the ongoing development of several drugs directed at complement activation.